Advancing Educational Practices: Insights from Global Innovations in Teaching and Learning - Haimi Mohd Adnan, Airil; Kusmawan, Udan (Universitas Terbuka, 2024)
This editorial review consolidates findings from eight pivotal articles featured in the International Journal of Research in STEM Education, which collectively explore innovative educational strategies aimed at augmenting teaching efficacy and student learning outcomes. The synthesis covers a diverse range of approaches including ICT-infused professional development, STEM-based and problem-based learning, and the effects of inquiry-based instruction. Through comprehensive analysis, the review articulates how these methodologies enhance educational practices across various settings, advocating for their broader implementation. The paper emphasizes the critical role of adaptable teaching methods and the integration of technological and interdisciplinary strategies in contemporary education systems. It proposes actionable insights for educators and policymakers on leveraging these approaches to foster an educational environment that is both dynamic and inclusive.